Evaluation of a three‐dimensional MR acoustic radiation force imaging pulse sequence using a novel unbalanced bipolar motion encoding gradient. Issue 3 (7th October 2015) - de Bever, Joshua T.; Odéen, Henrik; Todd, Nick; Farrer, Alexis I.; Parker, Dennis L.
Abstract : Purpose: MR guided focused ultrasound procedures require accurate focal spot localization in three dimensions. This study presents a three‐dimensional (3D) pulse sequence for acoustic radiation force imaging (ARFI) that efficiently localizes the focal spot by means of ultrasound induced tissue displacement over a large field‐of‐view. Methods: A novel unbalanced bipolar motion encoding gradient was implemented to maximize time available for motion encoding, reduce echo times, and allow for longer echo train lengths. Two advanced features, kz reduction factor (KZRF) and kz ‐level interleaving, were implemented to reduce tissue heating. Studies in gelatin phantoms compared the location of peak displacement and temperature measured by 3D MR thermometry. MR‐ARFI induced tissue heating was evaluated through a parametric study of sequence parameters and MR thermometry measurements during repeated application of ARFI sonication patterns. Sequence performance was characterized in the presence of respiration and tissue inhomogeneity. Results: The location of peak displacement and temperature rise agreed within 0.2 ± 0.1 mm and 0.5 ± 0.3 mm in the transverse and longitudinal direction, respectively. The 3D displacement maps were acquired safely, and the KZRF and kz ‐level interleaving features reduced tissue heating by 51%. High quality displacement maps were obtained despite respiration and tissue inhomogeneities. Conclusion: This sequence provides a safe, accurate, and simple approach to localizing the focal spot in three dimensions with a single scan. Magn Reson Med 76:803–813, 2016. © 2015 Wiley Periodicals, Inc.